Preface to the Special Issue on recent advances in the study of Equatorial Plasma Bubbles and Ionospheric Scintillation - Yuichi Otsuka; Luca Spogli; S. Tulasi Ram; GuoZhu Li (Earth and Planetary Physics, 2021)
The 2nd Equatorial Plasma Bubble (EPB) workshop, funded by the Institute of Geology and Geophysics, Chinese Academy of Sciences, and the National Natural Science Foundation of China, took place in Beijing, China during September 13–15, 2019. The EPB workshop belongs to a conference series that began in 2016 in Nagoya, Japan at the Institute for Space-Earth Environmental Research, Nagoya University, resulting in a special issue of Progress in Earth and Planetary Science that focused on EPBs. The main goal of the series is to organize in-depth discussion by scientists working on ionospheric irregularities, and solve the scientific challenges in EPB and ionospheric scintillation forecasting. The 2nd EPB workshop gathered almost 60 scientists from seven countries. A total of 20 invited and contributing papers focusing on ionospheric irregularities and scintillations were presented. Here we briefly comment on 10 papers included in this special issue.